Methods For Implementing the Microelectronic Operation of The Automatic Push-Button Circuit and The Arrow Control Circuit and The Control Block Npm-69-M - Ubaydullayev Saidazim Qahramon o’g’li (Zien Journals, 2022)
The article discusses the application and localization of electromagnetic relays, which are one of the most important elements in railway transport control systems. To solve these problems, the issues of modeling processes and finding a technical solution using microelectronic devices, improving efficiency and reliability are considered. To solve these problems, methods and technologies of microelectronic devices have been developed
Keywords: Railway transporti; electromagnetic relay; modelling; automatic button chain